Propuesta para la implementación de un Circuito de Actividades de Turismo Extremo en el Sendero del Área Nacional de Recreación los Samanes - Zambrano Celi, Jessica Mabel (2013)
Gamex, is an innovative business proposal of marketing in Guayaquil city, which is planned to become the first and best company which offer three funny, entertainment and risky products that elevate adrenaline in their customers. Its infrastructure will be built to the quality standards and will be guided by professionals who will guarantee the customer a high level of service and security, through excellent customer service and with a personalized guide. In this project we have done all the research and analysis necessary to know and understand if customers indistinct sex rate within a range between 18 and 45 years, have made such activities, which, in what places and each how long they have been made, also, to know if they would like to implement activities related to extreme sports in the Área de Recreación Los Samanes and the price for which they would pay. Then analyzed a feasibility study on the business proposal which was considered viable